Neural-Network-Based Methods for ARPES Data Processing (Review Article) - Pustovit, Yu.V.; Lytveniuk, Ye.P. (Ukrainian Journal of Physics, 2024)
In recent years, many developed upgrades of angle-resolved photoemission spectroscopy (ARPES) have significantly increased the amount of the obtained data. In this article, we briefly review the methods of processing of ARPES spectra with the use of convolutional neural networks (CNNs). In addition, we have made a short checkup of the potential application of CNNs that outperforms the existing methods or gives the possibility to achieve previously unachievable results.